Apathy and Executive Function in Healthy Elderly—Resting State fMRI Study - Kawagoe, Toshikazu; Onoda, Keiichi; Yamaguchi, Shuhei (Frontiers in Aging Neuroscience, 2017)
Apathy is a quantitative reduction in goal-directed behaviors, having three subtypes. Despite executive deterioration in healthy aging, researchers have not investigated the “cognitive-deficit” subtype of apathy in healthy populations, which would result from executive dysfunction. We hypothesized that a relationship between apathy and executive function would be found in healthy older adults, accompanied with neural deterioration with functional dysconnectivity between the striatum and frontal region as suggested by previous studies. A total of 100 healthy adults in a health examination system database were analyzed. The present study indicates that apathy is substantially associated with executive deterioration, which can be partially ascribed to decreased functional connectivity between the frontal and ventral striatum. Despite some limitations, our findings may contribute to research on healthy psychological aging.